2003
DOI: 10.1094/phyto.2003.93.4.397
|View full text |Cite
|
Sign up to set email alerts
|

Role of Host Sensitivity to Ptr ToxA in Development of Tan Spot of Wheat

Abstract: Pyrenophora tritici-repentis race 2 produces Ptr ToxA, a host-selective toxin previously described as a pathogenicity factor for tan spot on wheat. The objective of this research was to evaluate the role of host sensitivity to toxin, conditioned by a single dominant gene on chromosome 5BL, in the disease development by race 2. An F(2)-derived F(6) recombinant inbred population of 108 wheat lines, produced from crosses of toxin-sensitive, disease-susceptible cv. Kulm with the toxin-insensitive, disease-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
3
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 15 publications
3
58
3
3
Order By: Relevance
“…The evaluation was conducted individually with each isolate. Preparation of fungal cultures and inoculum and fungal inoculations were done as described by Friesen et al (2003). The fungus was cultured on V8-potato dextrose agar (PDA) in the dark for 5 days at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation was conducted individually with each isolate. Preparation of fungal cultures and inoculum and fungal inoculations were done as described by Friesen et al (2003). The fungus was cultured on V8-potato dextrose agar (PDA) in the dark for 5 days at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Anderson et al (1999) further reported that the same insensitivity gene, Tsn1, controls insensitivity in both durum and common wheat and this gene is located on chromosome arm 5BL. However, Friesen et al (2003) observed that segregation of insensitivity to necrosis induced by Ptr ToxA was controlled by a single gene, while the disease reaction of the recombinant inbred lines to spore inoculation by race 2 revealed that four to five genes may control resistance in the population. They observed that insensitivity to Ptr ToxA accounted for only 24% of the resistance to race 2 and concluded that Ptr ToxA was a virulence factor and not a pathogenicity factor.…”
Section: Pathogenic Variabilitymentioning
confidence: 99%
“…Friesen et al (2002), however, observed that wheat lines harboring mutations for insensitivity to Ptr ToxA induced by ethylmethane sulfonate were not necessarily resistant to race 1 (Ptr ToxA + or Ptr ToxC + ) of the fungus. In a recent study, Friesen et al (2003) reported that insensitivity to Ptr ToxA in F 2 -derived F 6 recombinant inbred lines did not result in complete resistance to race 2 (Ptr ToxA). The authors found that insensitivity to Ptr ToxA accounted for only 24% of the resistance to race 2 The solid line indicates the region coding for a putative signal peptide.…”
Section: Like Most Reported Host-specific Toxins the Toxins Of Pyrenmentioning
confidence: 99%